2013
DOI: 10.1182/blood-2012-08-447664
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide reduces survival of chronic lymphocytic leukemia cells in primary cocultures by altering the myeloid microenvironment

Abstract: Key Points Lenalidomide treatment of primary CLL/nurse-like cell cocultures resulted in significantly decreased viability of CLL cells. Lenalidomide increased IL-10 levels, activation of STAT1, expression of ICAM-1, and migration-related genes, and reduced CLL cell motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
(58 reference statements)
1
27
0
3
Order By: Relevance
“…18,28 We confirmed that lenalidomide reduced CLL survival in contact with NLCs from 54.2% to 44.5% after ten days (n=5; P<0.05) (Online Supplementary Figure S1), as reported by Schulz et al 17 The next part of the study was dedicated to the analysis of the effect of lenalidomide treatment on NLCs. First, we cultured PBMCs from 9 CLL patients for ten days with 0.5 mM or 1 mM lenalidomide or vehicle.…”
Section: Lenalidomide Induces Activation and Proliferation Of Nlcssupporting
confidence: 52%
See 3 more Smart Citations
“…18,28 We confirmed that lenalidomide reduced CLL survival in contact with NLCs from 54.2% to 44.5% after ten days (n=5; P<0.05) (Online Supplementary Figure S1), as reported by Schulz et al 17 The next part of the study was dedicated to the analysis of the effect of lenalidomide treatment on NLCs. First, we cultured PBMCs from 9 CLL patients for ten days with 0.5 mM or 1 mM lenalidomide or vehicle.…”
Section: Lenalidomide Induces Activation and Proliferation Of Nlcssupporting
confidence: 52%
“…26 The capability of lenalidomide to restrain monocyte migration is in line with studies demonstrating that this drug also interferes with CLL cell chemotaxis, suggesting that CORO1B upregulation and RhoH downregulation may be involved in migration impairment induced by lenalidomide in CLL cells and monocytes. 17,26 Conversely, high levels of RhoH in the presence of chemokine signals impair T-cell chemotaxis, explaining the opposite promoting effect of lenalidomide on T-cell migration. In treated CLL patients, lenalidomide would be expected to restrain monocyte migration towards chemokine gradients generated by CLL-infiltrated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morande et al (5) recently showed that NLCs were susceptible to Aplidin-induced death, suggesting that its anti-tumoral effects were from targeting CLL cells and NLCs simultaneously . Schulz et al (6) showed that treatment with lenalidomide changed the functional and phenotypic nature of NLCs by interfering with their nurturing properties.…”
mentioning
confidence: 99%